The effect of professional development on competitive advantage - Wesonga, Justus Nyongesa; Westhuizen, Johan Van Der (International Journal of Innovative Research and Scientific Studies, 2025)
One of the most important aspects of talent management is acknowledging that humans are the driving force behind organizations by utilizing resources to fulfill the requirements of customers. On the other hand, talent management must contend with increasing difficulties in the banking industry because of the intense competition for qualified people. The global talent race is intensified as a result of globalization, which makes talent shortages worse because skilled people are looking for opportunities all over the world. The purpose of the study was to investigate the connection between professional development and competitive advantage. A case study technique was utilized, and it was directed towards 146 people working at the KCB headquarters. Descriptive statistics, Pearson correlation analysis, and linear regression were utilized in the analysis of the primary data that was gathered through the dissemination of a questionnaire. According to the findings, there was a statistically significant positive correlation (r = 0.827; p-value = 0.000), such that professional development was responsible for explaining 68.4% of the variance in competitive advantage. According to the findings of the study, one way to improve the competitiveness of commercial banks is to make investments in professional development. The consequences of this extend to the optimization of staff management in Kenya’s commercial banking industry as well as the informing of regulatory frameworks.